LANDSCAPE PLANNING OF COMMUNITY-BASED AGRO- TOURISM AREA IN CISANDE TOURISM VILLAGE, CICANTAYAN SUB-DISTRICT, SUKABUMI DISTRICT - Fauziyya, Siva
A tourist village is a rural area integrated with tourist attractions, tourist amenities, public facilities, and the structure of community life along with the procedures and traditions that apply in it. Tourism villages have great potential to contribute to state revenues and reduce unemployment. Currently, village tourism is a development priority for the Ministry of Tourism and Creative Economy (Kemenparekraf) in collaboration with the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration (Kemendes PDTT). The Sukabumi District Government is also developing Sukabumi District into a tourism area that utilizes local resources and local wisdom, one of which is Cisande Tourism Village which won the 50 best tourism villages award at the 2021 Indonesian Tourism Village Award (ADWI) organized by Kemenparekraf.